2011
DOI: 10.1017/s1047951111000102
|View full text |Cite
|
Sign up to set email alerts
|

Protein-losing enteropathy: integrating a new disease paradigm into recommendations for prevention and treatment

Abstract: Protein-losing enteropathy is a relatively uncommon complication of Fontan procedures for palliation of complex congenital cardiac disease. However, the relative infrequency of protein-losing enteropathy belies the tremendous medical, psychosocial and financial burdens it places upon afflicted patients, their families and the healthcare system that supports them. Unfortunately, because of the complexity and rarity of this disease process, the pathogenesis and pathophysiology of protein-losing enteropathy remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 88 publications
(155 reference statements)
1
39
1
Order By: Relevance
“…This secondary disorder is characterized by profound loss of serum proteins into the gastrointestinal lumen caused by enteric mucosal injury, systemic inflammation, and venous or lymphatic obstruction [4]. The relative infrequency of PLE, combined with our rudimentary knowledge of the interplay between the cardiovascular and lymphatic systems, has hindered understanding of the pathophysiologic processes underlying this disease, as well as the development of effective therapy.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations
“…This secondary disorder is characterized by profound loss of serum proteins into the gastrointestinal lumen caused by enteric mucosal injury, systemic inflammation, and venous or lymphatic obstruction [4]. The relative infrequency of PLE, combined with our rudimentary knowledge of the interplay between the cardiovascular and lymphatic systems, has hindered understanding of the pathophysiologic processes underlying this disease, as well as the development of effective therapy.…”
Section: Commentmentioning
confidence: 99%
“…Transplantation is often the only reasonable option [5,6]. Historically, survival after diagnosis has been 50% at 5 years [4,7]. Nevertheless, a recent study reported 88% and 72% survival rates at 5 and 10 years, respectively, after diagnosis.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Th erapeutic measures in PLE are as follows: non-specifi c medical therapy, consisting in diets high in protein and low in fat, anti-congestive cardiovascular medical regimens, periodic albumin infusions and specifi c medical therapy, including the use of unfractionated heparin, corticosteroids, transcatheter therapy (dilation and/or stenting of obstructions in blood fl ow, coil embolisation of signifi cant aorto-pulmonary collaterals, fenestration of the circuit), heart transplant. Despite improvement in therapies used in Fontan patients with PLE, their prognosis has not signifi cantly improved and mortality related to PLE remains high [37].…”
Section: Nutrition Management Of Complications and Comorbiditiesmentioning
confidence: 99%